HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PROF. DR. V. L. RATUMBUYSANG PROVINSI SULAWESI UTARA (JURNAL KEPERAWATAN, 2018)
Abstract: Patients with mental disorders in rehabilitation periods treated by their own familyat home or outpatient need support to comply with the treatment program. Families may reduceanxiety caused by certain diseases and may reduce the temptation to non-compliance withcontinuity of treatment. The purpose of this study was to determine the relationship of familysupport with medication adherence. The research design was analytical descriptive with CrossSectional approach. The sampling technique used simple random sampling with 37 samples.The result of chi square statistic test with 95% confidence level (Î± = 0,05) obtained result pvalue 0,000